Language Learning Strategies of High School Students - alfian, Alfian (Media Akademika, 2011)
Research has shown that there are many factors, such as gender, age, motivation, performance, culture and achievement that relate to language learning strategies. The majority of research about language learning strategies has been conducted in various countries, especially in university settings. However, there are few studies about language learning strategies conducted in Indonesia. Meanwhile, English is a compulsory subject in Indonesia, but many students are unsuccessful in learning it. This may be closely related to the strategies that students in Indonesia use to learn English. My research investigates language-learning strategies of EFL students at high schools in Jambi, Indonesia. The research examines the relationship between strategies used and gender. The research also emphasizes examining the strategies used by successful and unsuccessful language learners. Therefore, the study was conducted into two parts. The first part included 80 participants who responded to a questionnaire on language learning strategies (SILL). In the second part, 8 participants who were successful and unsuccessful learners were interviewed in order to understand the strategies that are used. The SPSS version 9.0 for Windows was used to analyze the quantitative data from the questionnaire; the qualitative data from interviews was analyzed by using thematic analysis. The result shows that there are no differences of language learning strategies preference between males and females. However, successful students used more strategies than unsuccessful students, especially cognitive and metacognitive strategies. Furthermore, all students frequentlyused social, cognitive and metacognitive strategies. My research led me to conclude that this model of strategies can be used by unsuccessful language learners to help them learn English.